Respuesta :
-4x+y=-1
y=-1+4x
1+y=4x
then i used common sense and plugged the given answers in.
1+(3)=4(1)
4=4
D. (1,3)
y=-1+4x
1+y=4x
then i used common sense and plugged the given answers in.
1+(3)=4(1)
4=4
D. (1,3)
Answer:
(1,3)
Step-by-step explanation:
Given : [tex]-2x + y = 1[/tex]
[tex]-4x + y = -1[/tex]
To Find : Solve the following system of equations:
Solution:
[tex]-2x + y = 1[/tex] --1
[tex]-4x + y = -1[/tex] --2
Substitute the value of from 2 in 1
[tex]-2x + (-1+4x) = 1[/tex]
[tex]-2x -1+4x = 1[/tex]
[tex]2x = 2[/tex]
[tex]x = 1[/tex]
Substitute the value of x in 2
[tex]-4(1) + y = -1[/tex]
[tex]-4 + y = -1[/tex]
[tex] y =3[/tex]
Solution : (1,3)
Hence the solution of system of equations is (1,3)